Multiple brain abscesses due to Nocardia spp. in an immunocompetent patient (2020)
The infection by Nocardia spp is not common in immunocompetent patients. The empirical antimicrobial treatment directed by anatomical regions does not contemplate the particularities of the germ and the microbiological analysis is necessary for the specific treatment. We present the case of a previously healthy and immunocompetent patient, without known risk factors for Nocardia spp. infection, with evidence of involvement of the pulmonary parenchyma and the skin and subsequent development of multiple brain abscesses. © 2020 Instituto Nacional de Salud.